"We Could Do Better": Librarian Engagement in LGBTQ Collection Development in Small and Rural Public Libraries in the Southern U.S. Issue 6 (1st November 2020) - Betts-Green, Dawn
ABSTRACT: Although the LGBTQ community, from all appearances, maintains a strong connection to libraries as safe spaces, it is unclear whether the libraries themselves are providing relevant resources and services to the community. In addition, LIS research on LGBTQ patrons has centered on collection development how-tos and high level, broad suggestions without evaluating the actual state of the libraries' resources and services to these patrons. In this analysis, I found that what primarily affected what the libraries had on their shelves was an actively engaged librarian dedicated to proper collection development practices. Future research will be needed to better determine motivations and best practices for the larger group.